Intérêts nationaux et coopération multilatérale : le Canada et les banques de développement - Thérien, Jean-Philippe (Études internationales, 1992)
This article examines the place held by multilateral development banks in Canada's policy of external cooperation. It seeks to show how, in keeping with the overall logic of its aid policy, Canada's participation in these international financial institutions has resulted from a many-sided configuration of political, development al, and economic interests. The purpose of this article finds it s justification first of all in the fact that, by focusing mainly on bilateral assistance programs, the literature on Canadian aid has largely neglected the study of the many channels for distributing multilateral assistance.